KAJIAN BANDUL TERGANDENG PADA SEMBARANG SUDUT SIMPANGAN MENGGUNAKAN METODE RUNGE-KUTTA ORDE 4 - Fatimah Arrahma (Jurnal Fisika Indonesia, 2025)
This research will analyze the motion of a coupled pendulum in various arbitrary initial value angles. Computations use the fourth-order Runge-Kutta which are implemented on the coupled pendulum nonlinear differential equation. There are two main modes in the results: the in-phase mode and the out-of-phase mode. Computation results are in agreement with those in the main reference for some small angles. Results also showed that the computational program could be implemented for solving a coupled pendulum nonlinear differential equations on large angles so that it could resolve the limitation of the Computer Algebra System (CAS) method.